AB0405 ABNORMAL BLOOD LIPID METABOLISM IN PREMENOPAUSAL FEMALE SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS IS RELATED TO HYPERURICEMIA AND PROTEINURIA. (2nd June 2020) - Liu, H.; Lin, J. Z.; Cai, X.; MA, J. D.; Mo, Y.; Xie, M.; Dai, L.
Abstract : Background: 1. Hyperuricemia is often associated with abnormal lipid metabolism. We reported premenopausal female systemic lupus erythematosus (SLE) patients had elevated blood UA levels [1] . Do these patients also have hyperlipidemia? 2. Estrogen has certain effect on blood lipid metabolism, whether the blood lipid levels of premenopausal female SLE patients who have the background of hyperestrogen function are affected by estrogen and its receptors? Objectives: To investigate the relationships between blood lipids and serum UA level, estrogen receptors (ERs) as well as ER antibodies in premenopausal female SLE patients. Methods: 123 premenopausal female SLE patients (SLE group) were divided into normal CH group (n=93) and high CH group (n=30, CH>5.17mmol /l), and 40 healthy premenopausal females served as the control group. The blood lipid levels of the SLE group and the control group were compared, and the blood levels of lipid, UA, estrogen, ERs and ER antibodies were compared between the two SLE subgroups. Linear regression was used to analyze the influencing factors of blood CH. Results: 1. In SLE group, the blood level of TG was significantly higher than that of the control group (1.67±1.10 vs. 0.87±0.47, P<0.001), while the levels of blood CH, LDL, HDL were comparable to the control group (all with P> 0.05). 2. The mean blood CH level of the SLE patients with hyperuricemia was 5.57 ± 2.44mmol/l, which was significantly higher than that of patients with normal UA level (3.98 ± 1.30mmol / l, P <0.001). 3. The serum UA, CRE, CH, TG, LDL, and 24-hour urinary protein quantification (24h UPRO) in the high CH SLE subgroup were significantly higher than those in the normal CH SLE subgroup (all with P <0.05). There were no significant differences in serum estrogen, ERs and ER antibodies between the two subgroups, Table 1. 4. Linear regression showed that serum UA level and 24h UPRO were the dangerous effects of elevated blood CH in the premenopausal female SLE patients, Table 2. Conclusion: Compared with healthy female of the same age range, the premenopausal female SLE patients are more likely to have abnormal lipid metabolism, which is related to kidney damage and abnormal UA metabolism. References: [1]Haijun Liu, Xiaoyan Cai, Lie Dai, et al. Elevated uric acid levels in premenopausal female systemic lupus erythematosus patients: association with potential or existing renal damage. Eur J Inflamm, 2018, 16:1-6. Disclosure of Interests: None declared